Gene Transfer Agent Promotes Evolvability within the Fittest Subpopulation of a Bacterial Pathogen - Québatte, Maxime (Cell Syst, 2017)
The Bartonella gene transfer agent (BaGTA) is an archetypical example for domestication of a phage-derived element to permit high-frequency genetic exchange in bacterial populations. Here we used multiplexed transposon sequencing (TnSeq) and single-cell reporters to globally define the core components and transfer dynamics of BaGTA. Our systems-level analysis has identified inner- and outer-circle components of the BaGTA system, including 55 regulatory components, as well as an additional 74 and 107 components mediating donor transfer and recipient uptake functions. We show that the stringent response signal guanosine-tetraphosphate (ppGpp) restricts BaGTA induction to a subset of fast-growing cells, whereas BaGTA particle uptake depends on a functional Tol-Pal trans-envelope complex that mediates outer-membrane invagination upon cell division. Our findings suggest that Bartonella evolved an efficient strategy to promote genetic exchange within the fittest subpopulation while disfavoring exchange of deleterious genetic information, thereby facilitating genome integrity and rapid host adaptation.